Wound Healing Post-mesh Repair ? An Observational Study - M.N Lebbe; J Kularajasingham; P Dioso (Universitas Gadjah Mada, 2016)
This study identified the best surgical mesh repair techniques for inguinal hernia and prevalence of wound healing post-mesh repair. The cross-sectional study design used cluster sampling for data collection. Of the 120 respondents, 48.3% preferred anterior tension-free mesh repair and 49.2% Lichtenstein mesh repair, both identified as the common surgical techniques in eastern Sri Lanka. About 82.5% of the respondents (n = 99) healed while 17% (n = 21) had recurrence of hernia after one month. Nevertheless, 2.5% of the total respondents said that the hernia repaired after one month but less than two months; and 97.5% of the interviewees stated that they recovered in less than one month regardless of the surgical mesh repair technique. Respondents aged 30–39 faced little impact on healing time with mesh repair (p = 0.4393), while those aged 40–49 probably had also longer healing time (p = 0.3947). Recovering period differed significantly (p = 0.862), on pain ordiscomfort, especially when bending over, coughing or lifting heavy objects.